Three years after Rio : summary report on the FAO/UNEP regional workshops on implications of agenda 21 and the Forest Principles for Africa, Asia and the Pacific and Latin America and the Caribbean. (FAO RomeIT, 1995)
Highlights the progress achieved, experiences and main issues. Looks at the Tropical Forest Action Programme as an instrument for implementing UNCED agreements.
DC